SCREENING OF URINARY ISOLATES FOR THE PREVALENCE AND ANTIMICROBIAL SUSCEPTIBILITY OF ENTEROBACTERIA OTHER THAN ESCHERICHIA COLI.: Life Science-Microbiology - MEHTA, MANJULA; BHARDWAJ, SONIA; SHARMA, JYOTI (International Journal of Life Science and Pharma Research, 2013)
A total of 447 urine samples were processed in the Department of Microbiology . In this retrospective study 164 isolates 70.72% were E.coli and 16.46% were Gram negative bacteria other than E.coli, 12.80 % were Gram positive cocci. Antimicrobial susceptibility of uropathogens was tested by disc diffusion method. The Enterobacteria other than E.coli (n=27) were predominantly of Klebsiella over other isolates i.e Pseudomonas, Acinetobacter, Proteus, Citrobacter. On the other hand, among Gram positive cocci (n=21) there was predominance of Enterococcus (61.93%) over Staphylococci and Streptococci species. Antimicrobial sensitivity patterns of Enterobacteria other than E.coli revealed resistance to Penicillins followed by Quinolones like Nalidixic acid (33.3%), Nitrofurantoin (52.6%) and Co-trimoxazole (26.6%). On the other hand, Gram positive cocci showed maximum resistance towards Cephalexin (100%) followed by Nalidixic acid (85.7%), Co-trimoxazole (71.42%) and Norfloxacin (69.27%). However the drug of choice remains as Augmentin and other combination drugs for Gram negative bacteria whereas for Gram positive bacteria Nitrofurantoin, Augmentin and Linezolid remains as drug of choice, none was found to be resistant to Vancomycin